Application of wavelet analysis for updating Heinrich events age - T.E. Danova; B.V. Perelygin (Геофизический журнал, 2015)
Results of studies of spectral components energy reconstructed in the central part of Greenland air temperature transformed sequence data investigation by using wavelet analysis by the data of ice cores have been presented. Oscillation with fixed period as well as non-stationary oscillations has been revealed. Heinrich events age has been updated. Wavelet analysis allowed to correlate events with concrete climate phenomena and to estimate energy of these phenomena.